Evaluation of palygorskite on pellet quality, growth, antioxidant status and mineral contents of Chinese mitten crabs (Eriocheir sinensis). (6th January 2020) - Zhang, Ruiqiang; Du, Mingfang; Wen, Chao; Chen, Yueping; Jiang, Ying; Liu, Wenbin; Wang, Wenbo; Wang, Aiqin; Zhou, Yanmin
Abstract: This study evaluated the palygorskite inclusion effects on the pellet quality, growth, antioxidant status and mineral contents of Chinese mitten crabs. Crabs ( n = 640; initial average weight, 1.36 ± 0.02 g) were allocated into four groups with eight replicates of twenty crabs. A basal diet supplemented with 0, 10, 20 and 40 g/kg palygorskite was fed to crabs for 8 weeks respectively. Results exhibited that dietary addition of palygorskite enhanced the pellet process electrical energy consumption, improved the hardness and durability ( p < .05), reduced percentage of fines and dissolved weight loss of pellets (30, 60, 120, 240, 480 min; p < .05) in the water. Crabs had no differences on the weight gain, specific growth rate, feed conversion ratio, abdominal meat ratio and edible viscera index among the groups ( p > .05). Palygorskite inclusion decreased the MDA contents of edible viscera and abdominal meat ( p < .05) of Chinese mitten crabs. The ether extract contents of edible viscera in palygorskite inclusion groups were lower than that of the control group ( p < .05) in Chinese mitten crabs. Furthermore, palygorskite addition linearly increased the Fe level in the edible viscera and reduced tissue Pb and Cr ( p < .05) accumulations of Chinese mitten crabs. In conclusion, palygorskite inclusion could improve pellet quality, enhance the antioxidant capacity and Fe content of edible viscera, decrease the edible viscera ether extract level and tissue Pb and Cr accumulations without impairing the growth performance of Chinese mitten crabs, but increased the electrical energy consumption of pelleting.